Study on Intensive Care Unit Nutritional Protocol Based on Timing of National Health Insurance Coverage in Taiwan. (7th June 2021) - Lo, Shih-Ching; Hsiao, Yu-Chin; Chen, Ying-Ru; Lin, Hsing-Chun
Abstract: Objectives: Aggressive nutritional intervention may improve the outcomes of critically ill patients. Therefore, the National Health Insurance Administration (NHIA) in Taiwan revised its relevant fee schedule. On October 1, 2019, nutritional care items for intensive care unit (ICU) patients, covered by the NHIA under the category of nutritional care fees, were introduced to reflect real clinical needs. Methods: This retrospective cohort study was conducted in a medical center ICU. The study period was January 1, 2019 to May 31, 2020, before and after the start of national health insurance (NHI) coverage of new nutritional care items for ICU patients. A total of 5292 patients were recruited and divided into two groups based on timing of NHI coverage. There were 1591 patients included in the analysis (751 in the non-NHI group and 840 in the NHI group). In the NHI group, the following nutritional protocol was implemented: First visit was at 48hr following admission to the ICU with 2 follow up visits over the next 5 days, then 3 visits the following week. Patient demographics, daily nutritional data, and outcomes were collected to investigate the impact of this protocol. Results: Both groups were given the same nutritional intervention initially. However, there were significant differences in nutritional intervention following the incorporation of this treatment protocol in the ICU. Closely monitored nutritional intervention met critical requirements without overfeeding and led to shorter ICU stays (non-NHI 8.11 ± 6.69 days vs NHI 7.12 ± 7.43 days, p < 0.01). Conclusions: Nutritional care plan based on frequent assessments and interventions by dietitians is associated with reduced ICU stays for critically ill patients. Funding Sources: None.